Honeybees generalize among pollen scents from plants flowering in the same seasonal period - Pietrantuono, Ana Laura; Requier, Fabrice; Fernandez Arhex, Valeria Cristina; Winter, Josefina; Huerta, Guillermo Jose; Guerrieri, Fernando (The Company of Biologists, 2019)
When honey bees (Apis mellifera) feed on flowers, they extend their proboscis to absorb the nectar, i.e. they perform the proboscis extension response (PER). The presence of pollen and/or nectar can be associated with odors, colors or visual patterns, which allows honey bees to recognize food sources in the environment. Honey bees can associate similar, though different, stimuli with the presence of food; i.e. honey bees discriminate and generalize among stimuli. Here, we evaluated generalization among pollen scents from six different plant species. Experiments were based on the PER conditioning protocol over two phases: (1) conditioning, in which honey bees associated the scent of each pollen type with sucrose, and (2) test, in which honey bees were presented with a novel scent, to evaluate generalization. Generalization was evinced by honey bees extending their proboscis to a novel scent. The level of PER increased over the course of the conditioning phase for all pollen scents. Honey bees generalized pollen from Pyracantha coccinea and from Hypochaeris radicata. These two plants have different amounts of protein and are not taxonomically related. We observed that the flowering period influences the olfactory perceptual similarity and we suggest that both pollen types may share volatile compounds that play key roles in perception. Our results highlight the importance of analyzing the implications of the generalization between pollen types of different nutritional quality. Such studies could provide valuable information for beekeepers and agricultural producers, as the generalization of a higher quality pollen can benefit hive development, and increase pollination and honey production.